Scattering on a spherical shell. Comparison of 3-D elasticity and Kirchhoff shell theory results - Chang, Yao-Chang; Demkowicz, Leszek (Computer Assisted Methods in Engineering and Science, 1995)
The report is a continuation of [1]. The closed-form solutions of the scattering problem by the 3-D elasticity and Kirchhoff shell theories are investigated.